ANALISIS RISIKO KESELAMATAN KERJA METODE NATIONAL AERONAUTICS SPACE ADMINISTRATIONS TASK LOADING INDEX (NASA-TLX) BAGIAN PRODUKSI PABRIK MINYAK KAYU PUTIH (PMKP) KUPANG, MOJOKERTO - Euis Nurul Hidayah; Rizki Aziz Al Firdaus (EnviroUS, 2022)
PMKP Kupang is a Eucalyptus oil manufacturing factory that has been operating in Mojokerto Regency and is owned by Perum Perhutani. When doing their work, production employees get high enough of pressure so that the mental workload of employees increases. Therefore, it is necessary to analyze the risk of mental workload experienced by employees and the factors that influence it. So that PMKP Kupang can determine the right steps to fix this. The method used in this research is NASA-TLX which is a method to find out how much mental workload is. From the result of the NASA-TLX calculation, the workload value of all employees is 80.6 (very high) with the largest mental workload indicator in PMKP Kupang is the Effort (EF) factor of 270.